Assessing the Level of Employees’ Safety Performance in Northern Malaysian Small & Medium Manufacturings - Syazwan Syah, Zulkifly; Norwahida, Yaakub; Nur Syifa, Mohamad Zahir (2024)
In the pursuit of fostering workplace safety as an integral aspect of organisational vitality, present research delves into the landscape of safety performance within Small and Medium Enterprises (SMEs) in Malaysia. Despite facing resource constraints, the sector exhibit commendable dedication to safety, as evidenced by notably high levels of safety participation and compliance discovered among production workers through a cross-sectional study involving 107 professional respondents representing small and medium manufacturing firms in northern Malaysia. This study, addressing a crucial gap in research, sheds light on the need for continuous improvement strategies to sustain and amplify this positive safety culture within SMEs. The findings underline the significance of prioritizing safety initiatives, not only ensuring employee well-being but also fortifying the resilience and success of SME operations in Malaysia. Moving forward, it is imperative for these SMEs to invest in ongoing training programs and maintain open communication channels for safety concerns to further fortify their safety culture. Additionally, a longitudinal study could provide insights into the sustainability of these high safety performance levels over time, while exploring the impact of external factors on safety practices within these SMEs could offer valuable avenues for enhancing safety performance in the evolving business landscape.